Smallpox and pan-Orthopox Virus Detection by Real-Time 3′-Minor Groove Binder TaqMan Assays on the Roche LightCycler and the Cepheid Smart Cycler Platforms - Kulesh, David A. (American Society for Microbiology, 2004)
We designed, optimized, and extensively tested several sensitive and specific real-time PCR assays for rapid detection of both smallpox and pan-orthopox virus DNAs. The assays are based on TaqMan 3′-minor groove binder chemistry and were performed on both the rapid-cycling Roche LightCycler and the Cepheid Smart Cycler platforms. The hemagglutinin (HA) J7R, B9R, and B10R genes were used as targets for the variola virus-specific assays, and the HA and DNA polymerase-E9L genes were used as targets for the pan-orthopox virus assays. The five orthopox virus assays were tested against a panel of orthopox virus DNAs (both genomic and cloned) at the U.S. Army Medical Research Institute of Infectious Diseases (USAMRIID). The results indicated that each assay was capable of detecting both the appropriate cloned gene and genomic DNA. The assays showed no cross-reactivity to the 78 DNAs in the USAMRIID bacterial cross-reactivity panel. The limit of detection (LOD) of each assay was determined to be between 12 and 25 copies of target DNA. The assays were also run against a blind panel of DNAs at the Centers for Disease Control and Prevention (CDC) on both the LightCycler and the Smart Cycler. The panel consisted of eight different variola virus isolates, five non-variola virus orthopox virus isolates, two varicella-zoster virus isolates, and one herpes simplex virus isolate. Each sample was tested in triplicate at 2.5 ng, 25 pg, 250 fg, and 2.5 fg, which represent 1.24 × 10(7), 1.24 × 10(5), 1.24 × 10(3), and 1.24 × 10(1) genome equivalents, respectively. The results indicated that each of the five assays was 100% specific (no false positives) when tested against both the USAMRIID panels and the CDC blind panel. With the CDC blind panel, the LightCycler was capable of detecting 96.2% of the orthopox virus DNAs and 93.8% of the variola virus DNAs. The Smart Cycler was capable of detecting 92.3% of the orthopox virus DNAs and between 75 and 93.8% of the variola virus DNAs. However, all five assays had nearly 100% sensitivity on both machines with samples above the LOD (>12 gene copies). These real-time PCR assays represent a battery of tests to screen for and confirm the presence of variola virus DNA. The early detection of a smallpox outbreak is crucial whether the incident is an act of bioterrorism or an accidental occurrence.